What Influences Choice of Business-to-Business Connectivity Platforms?. Issue 4 (2nd October 2018) - Penttinen, Esko; Halme, Merja; Lyytinen, Kalle; Myllynen, Niko
ABSTRACT: Business-to-Business platforms provide connectivity and data exchange services and compete in several dedicated services, such as electronic invoicing (e-invoicing). Thus far, little research has examined the factors that influence firms' choice among competing platforms: Which platform features matter, and in what proportion in the decision maker's choice? To address this gap, we conduct an empirical study and triangulate with past theoretical explanations that have sought to account for the firm's choice. Based on the analysis, we formulate a platform selection model that includes nine features: (1) reach, (2) total cost, (3) usability, (4) ease of system integration, (5) implementation capability, (6) platform support for service improvement, (7) service customization, (8) platform reputation, and (9) long-term sustainability. We apply conjoint analysis using firms' selection data, collected from 282 firms that have recently made a purchase decision among e-invoicing platforms. All features except the vendor's implementation capability are found to significantly influence the platform choice. Two features—usability and reach—dominate the choice and account for nearly 50 percent of the likely outcome. We use cluster analysis to examine the effect of firm size on firms' preferences in platform features. As hypothesized, larger companies prefer interoperability, scale, and network effects, while smaller companies value local use efficiency and ease of use because they are more concerned with usability and cost. Our theoretical and managerial claims concerning platform choice highlight the difficulty of bootstrapping, the role of pricing and cost, the minor importance of implementation-related features, and the impact of longevity during platform contracting.